Pure talonavicular subluxation - Hassnaoui, Youssef El; Mohamed, Tazi; Hicham, Ait Benali; Mohamed, Shimi (International Journal of Research in Orthopaedics, 2025)
Talon-navicular dislocation of the tarsus is a rare injury that can be easily overlooked in emergency settings. This report details the case of a 26-year-old man who experienced a right foot injury due to a fall resulting in plantar hyperflexion. Initially misdiagnosed as an ankle sprain, further evaluation revealed a plantar sub-dislocation of the navicular bone, confirmed by radiological imaging.